2013
DOI: 10.1074/jbc.m113.497685
|View full text |Cite
|
Sign up to set email alerts
|

CD147, CD44, and the Epidermal Growth Factor Receptor (EGFR) Signaling Pathway Cooperate to Regulate Breast Epithelial Cell Invasiveness

Abstract: Background: CD147 induces invadopodia activity and invasiveness in breast epithelial cells. Results: CD147 forms complexes with CD44 and EGFR in lipid raftlike membrane domains and induces hyaluronan-CD44-dependent EGFR-Ras-ERK signaling that promotes invadopodia activity and invasiveness. Conclusion: CD147 induces signaling complexes critical to invasiveness in breast epithelial cells. Significance: CD147 is a potential therapeutic target and disease marker in breast cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
100
0
4

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 91 publications
(105 citation statements)
references
References 82 publications
1
100
0
4
Order By: Relevance
“…Previous studies have suggested a role for CD44 in invadopodia (Chabadel et al, 2007;Grass et al, 2013;Vikesaa et al, 2006). However, whether specific isoforms of CD44 are functionally crucial in invadopodia in cancer cells has not been determined.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have suggested a role for CD44 in invadopodia (Chabadel et al, 2007;Grass et al, 2013;Vikesaa et al, 2006). However, whether specific isoforms of CD44 are functionally crucial in invadopodia in cancer cells has not been determined.…”
Section: Discussionmentioning
confidence: 99%
“…The induction of MMP expression in fibroblasts in response to CD147 stimulation was shown to be dependent on downstream MAPK p38 signaling (Lim et al 1998). In addition to homotypic interactions between CD147 molecules on tumor cells and fibroblasts, it was proposed that up-regulation of CD147 in noninvasive breast cancer cells is sufficient to induce an invasive phenotype associated with high MT1-MMP activity in invadopodia (Grass et al 2012) as a result of enhanced EGFR-Ras-ERK signaling that is initiated through a signaling complex between CD147 and CD44 (Grass et al 2013).…”
Section: Pericellular Proteolysis In the Tumor Microenvironmentmentioning
confidence: 99%
“…41,67 In normal breast epithelial cells, upregulation of a cell-surface glycoprotein, CD147, increases EGFR activation leading to invadopodia formation and upregulation of MT1-MMP expression. 68 This effect is mediated by increased hyaluronan-CD44 signaling and interactions between CD147, CD44, and EGFR, which facilitates invadopodia formation and cancer cell migration. 68,69 Here, localization of growth factor receptors, which generate the necessary invadopodia-forming signals, with cell-surface proteins such as CD147 is critical for invadopodia formation.…”
Section: Growth Factorsmentioning
confidence: 99%
“…68 This effect is mediated by increased hyaluronan-CD44 signaling and interactions between CD147, CD44, and EGFR, which facilitates invadopodia formation and cancer cell migration. 68,69 Here, localization of growth factor receptors, which generate the necessary invadopodia-forming signals, with cell-surface proteins such as CD147 is critical for invadopodia formation.…”
Section: Growth Factorsmentioning
confidence: 99%